Pengaruh Penerapan Model Eliciting Activities (MEAs) terhadap Kemampuan Komunikasi pada Pembelajaran IPS Siswa Kelas 6 Sekolah Pioneer Depok - Adawiyah, Siti Robiatul; Muhyani, Muhyani; Alfaini, Noor Isna (MASALIQ, 2024)
This research was motivated by the aim of knowing the social studies learning of students in Grade 6 of Depok Pioneer School that has not been achieved, one of which is communication skills. One of the factors for students' lack of communication skills is simply listening to the teacher's explanation, then taking notes and solving practice questions. This can result in students' knowledge and understanding being limited to the information provided by the teacher. So that a learning model is needed that is applied, namely by applying Model Eliciting Activities (MEAs). The purpose of this study is to determine whether the application of Model Eliciting Activities (MEAs) affects communication skills in social studies learning in grade 6 of Depok Pioneer School better than student communication skills using conventional learning in grade 6 of Depok Pioneer School. This type of research is quasi-experimental research. Sampling was carried out using pre-test post-test control group design. The population in this study amounted to 24 grade 6 students of Depok Pioneer School. Social studies learning activities use Model-Eliciting Activities for experimental classes, while in control classes social studies learning activities use Conventional learning. Data analysis using an independent sample T-Test test on post-test values of the experimental group and control group results showed changes in communication in social studies learning after using Model Eliciting Activities (MEAs). Based on the results of the study, it can be concluded that students' mathematical communication skills using Model Eliciting Activities (MEAs) are better than students' communication skills using conventional learning in Grade 6 of Depok Pioneer School.